Faktor Sosiodemografi yang Mempengaruhi PHBS Rumah Tangga di Nagari Rawang Gunung Malelo - Novia Zulfa Hanum; Nurmaines Adhyka; Sri Mindayani (Universitas Jenderal Achmad Yani Yogyakarta, 2025)
Background: Clean and Healthy Living Behavior (PHBS) is a key health promotion and disease prevention strategy. However, household-level implementation remains suboptimal and is influenced by various sociodemographic factors.Objective: This study aimed to analyze sociodemographic factors influencing household Clean and Healthy Living Behavior. Methods: A cross-sectional study was conducted among 96 female respondents selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using univariate and bivariate analyses with the chi-square test. Results: The findings showed that 56.2% of households demonstrated poor PHBS practices. Education level (p=0.002), knowledge (p=0.000), and access to health services (p<0.05) were significantly associated with PHBS implementation. In contrast, income (p=0.753) and employment status (p=0.716) were not significantly related. The lowest-performing indicators included washing eating utensils in the river, smoking inside the house, and irregular physical activity. Conclusion: Household PHBS implementation is significantly influenced by education, knowledge, and access to health services. Strengthening health education and sustainable behavior change interventions is essential to improve PHBS practices.